Use of Indigenous Lactic Acid Bacteria for Industrial Fermented Sausage Production: Microbiological, Chemico-Physical and Sensory Features and Biogenic Amine Content - Federica Barbieri; Chiara Montanari; Chiara Angelucci; Fausto Gardini; Giulia Tabanelli (Fermentation)
The use of starter cultures in the meat industry is common, even if the number of available commercial cultures is limited, inducing product standardisation and microbial diversity reduction. On the other hand, some artisanal products relying on spontaneous fermentation can represent a source of isolation of new interesting strains. In this work, four LAB strains derived from Mediterranean spontaneously fermented sausages were tested as new starter cultures for the industrial production of fermented sausages, in comparison to a commercial starter culture. The products obtained were analysed for physico-chemical parameters, microbiota, biogenic amines and aroma profile. A consumer test was also performed to evaluate product acceptability. The strains induced different acidification kinetics. LAB counts showed high persistence when Latilactobacillus curvatus HNS55 was used as the starter culture, while the addition of Companilactobacillus alimentarius CB22 resulted in a high concentration of enterococci (6 log CFU/g), 2 log higher than in other samples. Tyramine was detected at concentrations of 150–200 mg/kg, except for in the sample produced with Lactiplantibacillus plantarum BPF2 (60 mg/kg). Differences were observed in the aroma profile, with a high amount of 2-butanone found in the samples obtained with Comp. alimentarius CB22. These latter sausages also showed the lowest score in terms of acceptability. This study allowed us to select new LAB strains for fermented sausage starter cultures, increasing the product diversification.